Hybrid Oxygen Carrier System of Formic and Acetic Acids for Soybean Oil Epoxidation - Shahrizan, Ahmad Shauqi Abrar (Scientific Research Journal, 2025)
Green chemistry’s commitment to sustainable and eco-friendly materials is exemplified by the epoxidation of soybean oil, which transforms a common crop into epoxidized soybean oil (ESBO), a versatile chemical asset. ESBO, a bio-based resource, serves as a plasticizer, stabilizer, and reactive diluent in industries like plastics and cosmetics. The study focused on the peracid method and hybrid oxygen carriers like formic and acetic acid to create ESB), a valuable chemical feedstock. This study examined the effect of reaction temperature on the epoxidation process found that the relative conversion to oxirane (RCO) value for the experiment at 65°C (40.68%) is higher compared to those at 75°C and 85°C, indicating that 65°C is the ideal temperature for the epoxidation process of soybean oil. The research highlights the importance of temperature in the kinetics of chemical reactions and the benefits of using a hybrid system for a more sustainable and eco-friendly approach to producing ESBO.